Pengaruh Gaya Kepemimpinan Terhadap Kepuasan Kerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kabupaten Ogan Ilir - Amtatu Syarifah; Agustina Hanafi; Parama Santati (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
This study aims to analyze the effect of leadership style on job satisfaction of employees in the Population and Civil Registration Office of Ogan Ilir Regency.The variable used in this research are job satisfaction as the independent variable and leadership Style as the dependent variable. The populations in this study were all employees of the Population and Civil Registration Office of Ogan Ilir Regency using a sample of 58 respondents. The research used a saturation sampling technique, collected primary data via questionnaires method. The analysis technique used was simple linear regression analysis. To validate the data, the validity test, reliability test, simple linear regression analysis, correlation coefficient analysis (r), coefficient of determination (R2) and t test were used in the research. The statistical Package for Social Science (SPSS) version 21 Program assistance tool was used to analyze the data. Based on the results of the analysis, it was concluded that leadership style had a positive and significant effect on job satisfaction of employees of the Population and Civil Registration Office of Ogan Ilir Regency. Keywords: Leadership Style, Job Satisfaction